POLAND’S INTERNATIONAL RELATIONS SCHOLARLY COMMUNITY AND ITS DISTINGUISHING FEATURES ACCORDING TO THE 2014 TRIP SURVEY OF INTERNATIONAL RELATIONS SCHOLARS - Czaputowicz, Jacek; Ławniczak, Kamil (Baltic Journal of Political Science, 2015)
In 2014, Poland was the first Central and Eastern European (CEE) country to be included in the Teaching, Research, and International Policy (TRIP) project. This article characterizes the Polish International Relations (IR) scholarly community and compares it with other IR scholarly communities throughout the world that also participated in the 2014 TRIP project. The 2014 TRIP survey, the Survey of International Relations Scholars (SIRS) asked Polish participants to identify: the strengths and weaknesses of the Polish IR discipline, influential Polish scholars and books published in Poland, and useful divergent study areas for practical policy purposes. Polish SIRS participants were also asked to share their research interests in both substantive areas and geographical regions, their opinions on economic and social issues, and their predictions concerning important developments in international policy. We concluded that while Polish scholars have much in common with their counterparts around the world, there are also significant differences. For example, Polish scholars identify themselves as more conservative than their international peers in social and ideological matters, more liberal in the economic sphere, and were more pessimistic about relations between the US and Russia in the near future.